The Position of the Child in the Life Experiences of Immigrant Survivors of Intimate Partner Violence: A Study of Service Providers’ Perspectives in Spain - Herrero-Arias, Raquel (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a global public health concern that has serious effects on the well-being of women and their children. Being a mother and an immigrant are critical factors that prevent women from seeking to end an abusive relationship. Evidence suggests that immigrant women see their children’s well-being and future as paramount while managing an abusive relationship. However, less is known about how women negotiate their children’s needs and interests when deciding whether to stay with or leave an abusive partner. Drawing on interviews with IPV service providers in Spain, this study aims to explore providers’ understandings of the position of the child in mothers’ reflections regarding whether to end an abusive relationship and of the implications of such positioning for mothers’ decision-making. The findings indicate that children hold two main positions in this process. In one, children are positioned as a trigger for mothers to stay with abusers. This occurs when women are economically dependent on their partner, when they think that their children need a father figure, or when the abuser plays a role in women’s migratory status within Spain. Second, children are positioned as a trigger for mothers to leave abusers when mothers see children as victims of violence or children in need of a mother figure. Framed by positioning theory, we discuss how we can understand the consequences of such positioning for immigrant women who are survivors of IPV and for service provision in this context. The implications of the findings for research, policy making, and professional decision-making are discussed.